Distributions and fluxes of methylmercury in the East/Japan Sea. (December 2017) - Yang, Jisook; Kim, Hyunji; Kang, Chang-Keun; Kim, Kyung-Ryul; Han, Seunghee
Abstract: The East/Japan Sea (EJS) is well ventilated to deep water via brine rejection from ice formations and thermohaline convection, resulting in a short overturning period in several decades. Due to these characteristics, the dissolved oxygen concentration in the EJS deep water is much higher (190–200 μg L −1 at 3000 m water depth) than that found at the same depths of the Northwestern Pacific (30 μg L −1 ) or anywhere in the Pacific Ocean. The total mercury (THg) and methylmercury (MeHg) distributions, and MeHg mass budgets were investigated to identify how the EJS's distinct circulation pattern affects Hg speciation. Whereas the THg concentration in the surface seawater (ranging from 0.20 to 1.2 pM, mean 0.59 ± 0.24 pM) showed no site variation between the Japan Basin and the Ulleung Basin, the MeHg concentration in the surface seawater was significantly higher (p < 0.05) in the Japan Basin (32 ± 24 fM) than in the Ulleung Basin (12 fM), with a south to north increasing gradient. This observation was supported by the mass budget estimation showing that upward diffusion as well as net methylation of Hg(II) was the primary source of MeHg in the surface seawater; the upward diffusion value was higher in the Japan Basin (3.2 nmol m −2 yr −1 ) than in the Ulleung Basin (1.9 nmol m −2 yr −1 ) due to the shallow thermocline depths in the Japan Basin. In contrast, the MeHg concentration in deep seawater (1000–3000 m) was similar between the Japan Basin (530 ± 87 fM) and the Ulleung Basin (610 ± 99 fM) and significantly (p < 0.05) higher than in the North Pacific (24 ± 40 fM) or North Atlantic (87 ± 96 fM) deep seawater. The Hg(II) methylation capacity, represented by the MeHg concentration normalized to apparent oxygen utilization, was also higher for the EJS deep water (0.0048) than the Northeastern Pacific (0.0030) and Northwestern Pacific (0.0025) intermediate waters, implying that the short overturning period of EJS may cause exclusively high MeHg concentrations in the deep water. Highlights: MeHg in deep water of EJS was significantly higher that at the same depth of North Pacific. There was a net methylation in the EJS deep water according to mass budgets estimation. A net methylation in deep water is attributable to the short overturning period of the EJS.